Measuring land degradation needs to be done from the ground up - Mutua, John Y.; Nijbroek, Ravic P. (2018)
Bush encroachment is a matter of growing concern in the semi-arid regions of Namibia. Locally adapted, long-term solutions for land restoration must be elaborated. It is crucial that local scientists are empowered to map and monitor the degradation process themselves, our authors maintain.